Industrial hazardous waste management law: a comparative study with United Kingdom law / Khairunnisah Sairah Abd Razak, Nur Azzuin Abdul Moati - Abd Razak, Khairunnisah Sairah; Abdul Moati, Nur Azzuin (2007)
In our research, we focused on the management of industrial hazardous waste in Malaysia by comparing it with the United Kingdom legislation. In Malaysia Department of Environment is fully responsible in matters relating to waste starting from the collection of waste up to the waste management. It was only a few years back when the waste management was privatized to a private sector. Kualiti Alam Sdn.Bhd. was incorporated as a* company to participate in the privatization of Malaysia's Scheduled Waste Management Project after the Government decided on the establishment of treatment and disposal facilities for toxic and hazardous waste in Malaysia to be built by private sector. In our research, we are going to look at various classification of waste in Malaysia and even in United Kingdom. From there we are going to move on by discussing on methods of disposing industrial waste in Malaysia. It is only in chapter four that we are going into depth of the law that governs waste management system both in Malaysia and United Kingdom. In the last chapter, after we've made comparison of waste management system in both countries, we give recommendation as how to overcome barriers to an efficient waste management in Malaysia.